1992
DOI: 10.1111/j.1432-1033.1992.tb17278.x
|View full text |Cite
|
Sign up to set email alerts
|

The mitochondrion in bloodstream forms of Trypanosoma brucei is energized by the electrogenic pumping of protons catalysed by the F1F0‐ATPase

Abstract: Bloodstream forms of Trypanosoma hrueei were found to maintain a significant membrane potential across their mitochondrial inner membrane (dym) in addition to a plasma membrane potential (d yp). Significantly, the dy, was selectively abolished by low concentrations of specific inhibitors of the FIFn-ATPase, such as oligomycin, whereas inhibition of mitochondrial respiration with salicylhydroxamic acid was without effect. Thus, the mitochondria1 membrane potential is generated and maintained exclusively by the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
145
0

Year Published

1993
1993
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 116 publications
(155 citation statements)
references
References 57 publications
10
145
0
Order By: Relevance
“…absence of glucose and presence of 2-oxoglutarate, a mitochondrial transmembrane potential could not be generated by hydrolysis of ATP produced by glycolysis (or by phosphagens since trypanosomes do not store phosphagens). Although the measured magnitude of the potential in long slender forms is similar to potentials measured in other cells (Nolan and Voorheis, 1992), this does not exclude the possibility that it is differentially regulated between the two bloodstream forms as suggested by other recent studies of rhodamine 123 uptake (Divo et al, 1993). These potentials were measured at a non-physiological temperature (30°C) and the actual magnitude of the potentials may be dependent upon temperature (Ter Kuile et al, 1992).…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…absence of glucose and presence of 2-oxoglutarate, a mitochondrial transmembrane potential could not be generated by hydrolysis of ATP produced by glycolysis (or by phosphagens since trypanosomes do not store phosphagens). Although the measured magnitude of the potential in long slender forms is similar to potentials measured in other cells (Nolan and Voorheis, 1992), this does not exclude the possibility that it is differentially regulated between the two bloodstream forms as suggested by other recent studies of rhodamine 123 uptake (Divo et al, 1993). These potentials were measured at a non-physiological temperature (30°C) and the actual magnitude of the potentials may be dependent upon temperature (Ter Kuile et al, 1992).…”
Section: Discussionmentioning
confidence: 89%
“…A recent paper by Nolan and Voorheis (1992) shows that the mitochondrion of bloodstream trypanosomes is energized by the mitochondrial FIFO-ATPase acting in the direction of ATP hydrolysis and utilizing ATP generated from glycolysis. These data, also supported by other workers (Vercesi et al, 1992), are not inconsistent with the work presented here.…”
Section: Discussionmentioning
confidence: 99%
“…We found cells that were morphologically stumpy and dykinetoplastid in the population at high frequency and further demonstrated that these cells specifically lacked a significant mitochondrial membrane potential as assessed by Mitotracker staining. This suggests a disruption of the function of the F1F0 ATPase, believed to be responsible for mitochondrial import in T. brucei (Nolan and Voorheis, 1992). Thus, the morphological and biochemical events of slender to stumpy transition can occur in the absence of the kinetoplast despite the fact that stumpy cells normally up-regulate transcripts for mitochondrial proteins and exhibit some metabolic adaptation to the procyclic form.…”
Section: Discussionmentioning
confidence: 98%
“…To establish that these cells did not retain kDNA-dependent mitochondrial activity, the population was stained using Mitotracker. This detects mitochondrial membrane potential, which in bloodstream forms requires protein subunits encoded in both the nucleus and kinetoplast (Nolan and Voorheis, 1992). Figure 6C shows that those cells with an obvious kinetoplast demonstrated a prominent mitochondrial staining with Mitotracker, indicating an extant mitochondrial membrane potential.…”
Section: Differentiation In Absence Of a Mitochondrial Genomementioning
confidence: 99%
See 1 more Smart Citation